Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer: k = 3
because p - 1 is a factor of the equation
=> at p = 1, p^4 + p² + p - k =0
with p =1, we have: 1 + 1 + 1 - k = 0
⇔ k = 3
Step-by-step explanation:
Answer:
Solution,
since the factor of f(p) = p-1
we know, f(p)= 0
p=1 (from remainder theorem)
now,
f(p) =p^4+p^2+p-k
0= 1^4+1^2+1-k
0= 1+1+1-k
0= 3-k
k=3
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.